Testing the savannah corridor hypothesis during MIS2: The Boh Dambang hyena site in southern Cambodia. (15th January 2018) - Bacon, Anne-Marie; Duringer, Philippe; Westaway, Kira; Joannes-Boyau, Renaud; Zhao, Jian-xin; Bourgon, Nicolas; Dufour, Elise; Pheng, Sytha; Tep, Sokha; Ponche, Jean-Luc; Barnes, Lani; Blin, Amandine; et al.
Abstract: The Boh Dambang karstic site in southern Cambodia, Kampot province, is a mammal bone-rich deposit in a hyena site. Very few hyena sites have been recovered in the Pleistocene of Southeast Asia, thus little information is known about the foraging abilities of hyenas during that period and their decline in the region, while the other hypercarnivores (tiger, leopard, and dhole) persisted until present day. To constrain the site we applied luminescence (red TL and single-grain OSL), ESR and U/Th dating methods to the sediments and faunal teeth, respectively. The resulting age estimates suggest that the site represents an accumulation of a young deposit with faunal teeth in the range of 25–18 ka that was last exposed to sunlight between 8 and 7 ka, and an older deposit containing older teeth (∼100–80 ka) that have been eroded from the upper caves in the system and incorporated into the younger deposit. Thus, the faunal age of 25–18 ka (MIS2), provides the best estimate for the age of the hyena site during LGM (26.5–19 ka). We analysed the assemblage of isolated teeth in terms of taxonomic diversity and abundance. The role of bone accumulators, either carnivores or rodents, has been precised through a taphonomic analysis. Diet was reconstructed through measurement of δ 13 C values of tooth enamel. The taphonomic analysis reveals that the hyenas were the main bone accumulators at Boh Dambang. Porcupines were aslo a factor in the accumulation of remains. The results show that the spotted hyenas hunted large-sized herbivores (>600 kg), in a mixed environment dominated by grassland. These data along with evidence from other Pleistocene faunas from Southeast Asian mainland, in terms of prey preference of hyenas ("rhinoceroses versus large bovines") also reveal marked differences in relation to habitat type. Possible causes of the decline of the spotted hyena in the Indochinese sub-region (hypercarnivory, high trophic level, comparable foraging strategies with hunters-gatherers, and climatic changes) are tentatively proposed at this point. Highlights: Boh Dambang is a hyena site in a karstic context, in southern Cambodia. The mammalian fauna is dated to 25–18 ka (OSL, ESR-U/Th). Diet preference of the spotted hyena is analysed using δ 13 C values of tooth enamel. The reconstruction of habitat show a mixed environment dominated by grassland. Possible causes for the decline of the spotted hyena are proposed.